2002
DOI: 10.1159/000056158
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP-Induced Reduction in Cardiac Myocyte Function Is Partially Mediated by Activation of the Sarcoplasmic Reticulum Ca<sup>2+</sup>-ATPase

Abstract: We tested the hypothesis that the mechanism through which cyclic GMP reduces cardiac function is mediated by activation of the sarcoplasmic reticulum Ca2+-ATPase (SERCA). Cardiac myocytes were isolated from New Zealand white rabbits (n = 11). Individual ventricular cells were stimulated by electrical field stimulation. The maximal rate of cell shortening and percentage shortening were measured with a video edge detector. Thapsigargin (10–8 mol/l) was used as a specific inhibitor of SERCA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…The integrated reduction in myofibril contractility, induced by cGMP in response to metabolic stress, decreases tissue indices of energy demand, including force of contraction (31), tension (32), fractional shortening (33), and maximum rate of shortening (34).…”
Section: Resultsmentioning
confidence: 99%
“…The integrated reduction in myofibril contractility, induced by cGMP in response to metabolic stress, decreases tissue indices of energy demand, including force of contraction (31), tension (32), fractional shortening (33), and maximum rate of shortening (34).…”
Section: Resultsmentioning
confidence: 99%
“…This is coincided with the notion that sustained cellular cGMP induces apoptosis, delays cell cycle progression and usually produces negative functional and metabolic effects on cardiomyocytes. 22) Perturbations in mitochondrial physiology appear to play an important role in apoptosis. 23) Commonly, Dy m dissipation is triggered by permeability transition pore (PT pore) opening and then cells lose the ability to synthesis of mitochondrial ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in our laboratory suggested that cyclic GMP signaling affects myocyte function, in part, through phosphorylation of phospholamban, which regulates SERCA activity [2,5]. In the current study, we used a genetic approach using phospholamban knockout (PLB-KO) mouse myocytes to test the hypothesis that the negative functional effects of cyclic GMP on cardiac myocytes were mediated through cyclic GMP-dependent regulation of phospholamban (PLB) and subsequent changes in intracellular calcium transients.…”
Section: Introductionmentioning
confidence: 99%
“…Elevation in the level of cyclic GMP decreases myocyte oxygen consumption and myocyte contraction in rabbit, mouse and canine hearts and cardiac ventricular myocytes [2,3]. The negative effects of cyclic GMP are mainly mediated through the cyclic GMP-dependent protein kinase and this could reduce intracellular Ca 2+ by activation of the sarcoplasmic reticulum Ca 2+ -ATPase (SERCA) [4,5]. Cyclic GMP mediated signaling may also involve phosphorylation of ryanodine receptors (RyRs) by cyclic GMP-dependent protein kinase and/or indirectly regulate RyRs by changing the cytosolic levels of RyRs through cADP-ribose [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation